The Effect of Nature-Themed English Songs on Humanistic Values Development in Early Childhood Education - Aryanti, Nurul; Lestari, Pratiwi; Ardiansyah, Welly (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
The quasi-experimental study examined the effectiveness of nature-themed English songs in developing humanistic values among children in Early Childhood Education (PAUD). The population consisted of children aged 4–5 years, a critical stage for social, emotional, and character development. The research was conducted at Chatya Manis PAUD, and a non-probability sampling method was used. Two existing PAUD classes were deliberately selected because they were comparable in age, gender distribution, and baseline humanistic values. One class served as the experimental group, while the other functioned as the control group. Statistical analyses confirmed that no significant differences existed between the groups at the pretest stage, ensuring a valid comparison. The sample comprised 60 children aged 4–5 years (M = 4.6, SD = 0.52), evenly divided into two groups of 30 children, with a balanced gender composition. The experimental group participated in an eight-week intervention, whereas the control group continued with the standard PAUD curriculum. Data were analyzed with independent t-tests and hierarchical linear regression. Results show that the experimental group demonstrated a statistically significant and substantially greater improvement in humanistic values (M=4.25, SD=0.38) compared to the control group (M=3.45, SD=0.42), t(58)=7.84, p<.001, with a very large effect size (Cohen's d=1.99). Hierarchical regression confirmed the song intervention was a strong and unique predictor (β=0.74, p<.001), explaining 54% of the variance (ΔR²=0.54) in outcomes after controlling for age and gender. In conclusion, nature-themed English songs are a highly effective, evidence-based pedagogical tool for promoting humanistic character development in PAUD. The study recommends the systematic integration of such musical activities into early childhood curricula to cultivate empathy, environmental appreciation, and curiosity.